Automation and the value of time in passenger transport - Mogens Fosgerau (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2019)
This paper reiterates the basic principles and rationale for valuing travel time savings. It explains the type of impacts that the valuation of travel time savings intends to capture and discusses whether and how those fundamental principles continue to hold with automation and increased possibility of productive time use while travelling. The paper also discusses implications for traffic management and urban form that follow from increased in-vehicle productivity.
Keywords: 330